Efforts to Improve students Learning Outcomes By using Google Classroom Covid 19 The subject Teorema Phytagoras - Fajar Isman; Asri Widiatsih (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
Abstrack Teachers and lecturers are educational, but have duties, among others, to improve performance in classroom action research in improving student learning outcomes for mathematics subjects. This research is a PTK which is often called PTK by using the Lut lewin model which consists of four stages 1. Planning 2. Action 3. Observation and 4 Reflections. The purpose of this research is to improve student learning outcomes by using google classroom for class VIII at SMPN One Atap Kandang Kapongan, Situbondo Regency. The number of students is 20 students. In data collection techniques using observation, documentation and tests and analysis techniques through models with the order of presenting information and drawing conclusions. The results of this study were to improve student learning outcomes for the subject of the Pythagorean theorem, this can be seen from the results of the percentage of student learning outcomes in cycle I reached 60% while cycle II reached 85% so that student learning outcomes tied 20% with KKM number 70 out of 100. of the complete cycle I, there are 12 students while cycle II 17 students. So it can be concluded that usinglearning media google classroom can improve student learning outcomes with the subject of the Pytagoras Theorem for class VII SMPN Satu Atap Kandang, Situbondo Regency 2020-2021. Keywords: learning outcomes, google classroom, Phytagoras